IMPROVING THE ADOLESCENTS’ CAPACITY WITH VIDEO AND DISASTER MITIGATION SIMULATION-BASED TRAINING - Dewi, Ervi Rachma; Caesar, David Laksamana; Ulfa, Maria; Wachid, Abdul; Aziza, Naisya Zaidatul (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
High cliffs in the mountainous area surround the village of Rahtawu make the area more vulnerable and prone to natural disasters. This community service empowered the youth in Rahtawu Village regarding disaster mitigation with interactive training method-based videos and disaster response simulations. The respondents to the community service activity consisted of 55 adolescents from four hamlets in Rahtawu Village. The stages of the community service activities included pre-test, video-based training, disaster mitigation simulation, and post-test. The questionnaire contains 20 questions about adolescents' knowledge and attitudes regarding disasters, disaster prevention, and the role of adolescents during disasters. The community service activity resulted in an increase in knowledge and attitudes both before and after the intervention, taking the form of video-based training and disaster mitigation simulations. The adolescents were very enthusiastic about following each discussion topic. Adolescents Understood the importance of disaster mitigation. The researchers expect these adolescents can spread knowledge about disaster mitigation in their surroundings.